Some Moot Points on the 1980 Hague Abduction Convention - Lowe, Nigel (Victoria University of Wellington Law Review, 2015)
This article discusses the Hague Convention on the Civil Aspects of International Child Abduction which, despite having been in existence for over 30 years, continues to present a number of uncertainties for Contracting States. The article focuses on the issues around appealing return orders after a child has been taken out of the jurisdiction, the concept of “habitual residence”, and the non-enforcement of return orders with reference to recent case law from the United States, United Kingdom, New Zealand and the European Union.